The hybridization of journalistic cultures : a comparative study of journalistic role performance - Mellado, Claudia (2019)
Influential research on comparative media systems identifies distinctive models according to which certain countries—particularly advanced democracies—share key features in their journalistic cultures. Revisionist literature has not only emphasized the limitations of such models, but also highlighted the hybridization of journalistic cultures elsewhere. This article tests the hybridization thesis, analyzing the presence of six journalistic roles in print news from 19 countries (N = 34,514). Our findings show patterns of multilayered hybridization in the performance of professional roles across and within advanced, transitional, and nondemocratic countries, with journalistic cultures displaying different types of hybridity that do not resemble either existing ideal media system typologies or conventional assumptions about political or regional clusters. The implications of these findings for future studies are discussed.